Józef Wittlin and the European Exile - Marín Villora, Trinidad (Eslavística Complutense, 2015)
This paper aims to study the exile of the Polish author Józef Wittlin in the context of the European exile started after Hitler´s rise to power in 1933. It will be analyzed his relationship and collaboration with other European exiles, specially German-speaking authors, as well as the main spaces of confluence of exiles and the problems that the exiled writers faced at that time.